COVID-19 in Workplace Settings: Lessons Learned for Occupational Medicine in the UK - Agius, Raymond (La Medicina del Lavoro, 2023)
This paper addresses lessons learned from the COVID-19 pandemic from a UK Occupational Medicine perspective to permit comparison with other national accounts. In spite of good prior research and statute, the necessary resources to protect workers’ health were seriously lacking when the pandemic struck. Weak public health guidance, which did not recognise dominant airborne transmission, was applied to workplaces, leaving workers and others unprotected, especially in respect to Respiratory Protective Equipment (RPE). The Health and Safety Executive (HSE) as regulator was lacking, for example, in not producing guidance to protect HealthCare Workers (HCW) who were amongst the most at risk. The UK COVID-19 Public Inquiry should address shortcomings such as these, but recommendations must be accompanied by robust means to ensure appropriate implementation. These should range from substantial measures to improve indoor air quality, to a permanent pandemic management organization with adequate resources. The enforcing authority has to be obliged to publish more specific workplace guidance than the public health authorities. Occupational medicine as a discipline needs to be better prepared, and hence to assert its responsibility towards high standards of workers’ health protection. Future research has to include investigating the best means of mitigation against airborne infection and the management of post-acute covid sequelae.